2003
DOI: 10.1097/00126450-200307000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Affiliated Pediatric Urgent Care Clinics

Abstract: This study analyzed whether a children's hospital urgent care clinic helped increase market share. Patient demographics and utilization patterns between the suburban clinic and urban emergency department were compared over a three-year period (July 1999 to June 2002). Using data from a standardized billing form, all patient visits (clinic: 36,924; emergency department: 160,888) were analyzed. Variables included patient visitation date, age, gender, race, primary insurance carrier, primary diagnosis, and primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…4 In some areas, urgent care centers specializing in pediatrics have opened, some of which are affiliated with a children's hospital. 5 A previous study done at our institution evaluated the clinical appropriateness of transfers from general urgent care centers into our pediatric ED. 6 That study showed that a significant proportion of transfers were discharged home with minimal ED resource utilization, suggesting that those transfers were not necessary.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 In some areas, urgent care centers specializing in pediatrics have opened, some of which are affiliated with a children's hospital. 5 A previous study done at our institution evaluated the clinical appropriateness of transfers from general urgent care centers into our pediatric ED. 6 That study showed that a significant proportion of transfers were discharged home with minimal ED resource utilization, suggesting that those transfers were not necessary.…”
mentioning
confidence: 99%
“…A 2009 survey of approximately 500 urgent care centers found that only 9.6% had a pediatrician on staff, none of whom were full-time 4 . In some areas, urgent care centers specializing in pediatrics have opened, some of which are affiliated with a children’s hospital 5 …”
mentioning
confidence: 99%